2019
DOI: 10.1371/journal.pone.0209965
|View full text |Cite
|
Sign up to set email alerts
|

Limited effects of the maternal rearing environment on the behaviour and fitness of an insect herbivore and its natural enemy

Abstract: The maternal rearing environment can affect offspring fitness or phenotype indirectly via ‘maternal effects’ and can also influence a mother’s behaviour and fecundity directly. However, it remains uncertain how the effects of the maternal rearing environment cascade through multiple trophic levels, such as in plant-insect herbivore-natural enemy interactions. Pea aphids (Acyrthosiphon pisum) show differential fitness on host legume species, while generalist aphid parasitoids can show variable fitness on differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
0
6
1
Order By: Relevance
“…Previous studies investigating the relative importance of maternal effects and current environment in aphids indicated no role of maternal effects on mass or reproduction (McLean et al, 2009;Hu et al, 2016;Slater et al, 2019), or limited effects on mass (Hu et al, 2018), when offspring were reared in low-stress environments. However, each of these studies transferred aphid offspring to host plant species (or varieties) different than that of their mothers to test the consequences of host-switching, whereas we explored the effects of maternal resource stress (host plant quality or crowding) on offspring within the same host species.…”
Section: Maternal Effects Mediated By Conspecific Density In Second Generationmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies investigating the relative importance of maternal effects and current environment in aphids indicated no role of maternal effects on mass or reproduction (McLean et al, 2009;Hu et al, 2016;Slater et al, 2019), or limited effects on mass (Hu et al, 2018), when offspring were reared in low-stress environments. However, each of these studies transferred aphid offspring to host plant species (or varieties) different than that of their mothers to test the consequences of host-switching, whereas we explored the effects of maternal resource stress (host plant quality or crowding) on offspring within the same host species.…”
Section: Maternal Effects Mediated By Conspecific Density In Second Generationmentioning
confidence: 93%
“…To test the intergenerational effects of resource quality, we grew host plants at low or high levels of fertilizer, which has been shown to increase plant nitrogen (Awmack & Leather, 2002;Fagan et al, 2002;Slater et al, 2019), height, and biomass in Asclepias species (Hanson et al, 2017). Aphids tend to be limited by nitrogen, and the addition of nitrogen through fertilizer has been shown to benefit aphid fitness (Awmack & Leather, 2002;Fagan et al, 2002;Slater et al, 2019). In addition, NPK fertilization can reduce cardenolides, compounds produced by milkweed to deter herbivores (Agrawal et al, 2012).…”
Section: Experimental Designmentioning
confidence: 99%
“…The impact of natal effects seems to be dependent on the studied insect taxonomic group. There was, for example, a limited effect of the maternal rearing environment on behaviour in pea aphids (Slater et al, 2019), but a significant association between natal origin and oviposition preference in water lily beetles (Verschut et al, 2017). It should be noted that we used wild-caught females for the preference test and we therefore have no control of potential natal effects -i.e., we do not know which host plants the females fed on as larvae.…”
Section: Host Plant Preference and Effects On Developmental Rate Anmentioning
confidence: 99%
“…Several studies have demonstrated the potential for parasitoids to experience a penalty—in the form of increased time for host location and handling—when switching between aphid hosts differing in quality (e.g. Slater, Gilbert, Johnson, & Karley, 2019) and illustrate that parasitoids can distinguish between parasitism‐resistant and ‐susceptible types due to symbiont‐conferred effects on aphid defensive behaviour or pheromone production susceptibility to parasitism (e.g. Dion, Polin, Simon, & Outreman, 2011; Oliver et al, 2012).…”
Section: Introductionmentioning
confidence: 99%